Hypolipidemic effect of aqueous extract from the leaves of Artocarpus altilis "breadfruit" in Rattus norvegicus induced hyperlipidemia (Scientia Agropecuaria, 2013)
The present study aimed to demonstrate the hypolipidemic activity of aqueous extract of leaves of breadfruit, Artocarpus altilis, in a model of acute hyperlipidemia induced with triton X-305, using Rattus norvegicus specimens males, mean weight 204.5 g, who were orally administered 0.05 g/100g and 0.2 g/100 g of aqueous extract of A. altilis; included a negative control group received physiological saline and hyperlipidemic positive control group. After 24 hours of administering the treatments were made measurements of the concentrations of serum cholesterol and triglycerides. Found significant reductions (p < 0.01) in both cholesterol and triglyceride levels relative to the positive control group. We also found a significant difference (p < 0.01) between triglyceride concentrations of the animals treated with both doses of the aqueous extract of A. altilis. Conclude that the aqueous extract from the leaves of A. altilis has hypolipidemic effect at the doses tested for the model of hyperlipidemia induced with triton X-305.
Keywords: Artocarpus altilis; hypolipidemic; cholesterol; triglycerides